CONSTRAINTS FACED BY THE POULTRY FARMERS IN REARING AND MARKETING OF POULTRY IN DIBRUGARH DISTRICT OF ASSAM - Borthakur, Bikash; Hazarika, Pulin; Saharia , Kamala Kanta (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
A survey of 100 farmers revealed that lack of suitable marketing facility to receive remunerative price of the poultry products was the major constraints reported by 100% farmers, followed by high cost of chick and feed (80%), incidence of disease like CRD and Ranikhet (60%).
Keywords: Poultry Farmers; Constraints; Rearing; Marketing; Dibrugarh